PELATIHAN TEKNIK VIDEO DOKUMENTASI UNTUK STAF KECAMATAN DAN KELURAHAN GROGOL PETAMBURAN - Ruby Chrissandy (PROSIDING SERINA, 2021)
The third level administrative subdivision Kecamatan Grogol Petamburan have seven urban village with seventy-three hamlets (Rukun Warga) and eight hundred sixty-three neighbourhood (Rukun Tetangga) in its territory. This sub-district is led by Drs. Didit Sumaryanta. Kecamatan Grogol Petamburan has a lot of community service activities and needs videos documentation to support the publication of its activities, several videos are uploaded on the Kecamatan Grogol Petamburan YouTube channel. There are 14 subscribers with 7 activity videos uploaded 3 years ago, but the videos are not satisfactory due to a lack of insight into video production techniques, video editing applications and limited tools. The UNTAR PKM team helped provide solutions by providing training video documentation production techniques. The activity was attended by 16 participants from the sub district and urban village Grogol Petamburan. All materials support the improvement of participants' ability to make good video documentation. This knowledge is expected to help participants know and understand the production and post-production of video documentation.